Effects of Coworker Incivility on Task Performance and CWB through Work Engagement: Perceived Supervisor Support as the Moderator - Kim, Youngsin; Park, HyungIn (Korean Journal of Industrial and Organizational Psychology, 2022)
This study investigated moderating effects of perceived supervisor support (PSS) on the indirect path from coworker incivility to task performance and two kinds of counterproductive work behaviors (CWBs), CWB directed toward the organization (CWB-O) and toward individuals (CWB-I), through three facets of work engagement (vigor, dedication, and absorption). Participants were 243 employees in South Korea who worked with at least one coworker and completed a two-wave online survey with a one-month interval. Results indicated that PSS had significant moderating effects on the relationships of vigor with task performance and of absorption with CWB-O, but not on the other relationships. Moreover, moderated mediating effects were observed in these two models. In addition, coworker incivility directly explained CWB-O and CWB-I even after controlling the other variables. Based on these findings, we discussed study implications and suggestions for future research.